2011
DOI: 10.1177/0739456x11414715
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Diversity in Urban Planning Education and Practice

Abstract: Planning needs more diversity if it is to have legitimacy. Diversity can be achieved through more diverse faculty and students who become practitioners, and by increased scholarship that addresses diversity. In this essay, we examine the trends in scholarship about diversity in planning and the barriers to increasing faculty and students of color in planning schools, and we propose ways to move forward. We conclude that planning must increase the number of faculty of color in tenured and tenure-track positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…For example, Whites are overrepresented in city planning professions (e.g.,Vazquez, 2002) as well as among faculty and students in urban planning graduate programs(Sweet & Etienne, 2011).9 As in Study 2a, the house evaluation measure indexes factors potential homebuyers usually consider when initially evaluating a home. A principal components factor analysis without rotation confirmed that all five items in this updated measure loaded onto a single factor (loadings in parentheses): house liking (.87), others' interest (.77), change needed (.63), poor investment (.75), and make offer (.82).…”
mentioning
confidence: 99%
“…For example, Whites are overrepresented in city planning professions (e.g.,Vazquez, 2002) as well as among faculty and students in urban planning graduate programs(Sweet & Etienne, 2011).9 As in Study 2a, the house evaluation measure indexes factors potential homebuyers usually consider when initially evaluating a home. A principal components factor analysis without rotation confirmed that all five items in this updated measure loaded onto a single factor (loadings in parentheses): house liking (.87), others' interest (.77), change needed (.63), poor investment (.75), and make offer (.82).…”
mentioning
confidence: 99%
“…How can planners develop cultural competency to integrate "difference" into planning practices and participatory actions in a comprehensive way? (Agyeman & Erickson, 2012;Sweet & Etienne, 2011;Vazquez, 2009). This article examines a health action research project implemented in the Swale District (Sittingbourne, Kent, UK) in 2009 -11.…”
Section: Introductionmentioning
confidence: 94%
“…The ACSP's Planners of Color Interest Group, founded by faculty of color, has formalized its role within ACSP. Furthermore, research and discussions about moving the field forward have focused on the underrepresentation of students and faculty of color (Forsyth, 1995;Iraz abal et al, 2011;Sweet & Etienne, 2011;Wubneh, 2011), pointing to the need for multicultural curriculum, recruitment, and retention programs for people of color and tenure and promotion support. These efforts are creating new venues that can help planners think critically about how the planning profession and planning organizations reproduce racial disparities.…”
Section: How Can Planners Pursue Repo?mentioning
confidence: 99%